EFL Students’ Perceptions on Using Picture Strip Story in Learning Speaking Skills - Bambang purnama; Roi Boy Jon; Ari Safar Wadi (International Journal of English and Applied Linguistics (IJEAL), 2022)
Using a method in the teaching-learning process that is by the condition of students to maximize the purpose of English learning. In the Indonesian context, limited time to learn speaking skills for EFL students is still one of the issues found in the classroom. The method that can be used to maximize the process of teaching and learning is picture strip story. This research aimed to find out the EFL students' perception of using picture strip stories in learning speaking skills. The participants of this research consisted of twelve students. The writer collected data by using focus group discussions with a semi-structured interview. The researcher used data display, condensation, drawing, and verification in data analysis. The result of this research was positive perceptions from EFL students toward using picture strip stories in learning speaking skills, such as improving students' confidence to speak with others, developing the students' proficiency in language competence, improving students' motivation, and adding the eggar the students to learn speaking skills.